IMPROVE THE QUALITY OF COOPERATION WORK CONSULTATION FOR STUDENTS OF PHU THO ELEMENTARY SCHOOL - Thu, Le Phong; Thi Mai Lan, Bui (The journal of contemporary issues in business and government, 2022)
The problem of coordination in school counseling for primary school students has been painstakingly studied by scientists and researchers in education and has shown the actual contents of the work. We coordinate consultation and essential requirements for principals and teachers in charge of this work, such as roles, tasks, and responsibilities. Practice shows the role and influence of educational administrators' education for perception and thinking in coordination forces.